Application of functional games in the pre-protetization of patient with post-osteosarcoma hip disarticulation: case study (Research, Society and Development, 2022)
Osteosarcoma (OS) is a malignant neoplasm that affects bone tissue, with no apparent cause, affecting the appendicular skeleton, especially the femur and tibia of children and adolescents. Treatment consists of surgeries of tumor resection or limb amputation associated with chemotherapy. Strengthening, stretching, proprioception, balance and coordination, aiming at future, independent walking. It is believed that rehabilitation through the use of functional play programs in rehabilitation such as Xbox360 Kinect® offers different stimuli compared to conventional techniques of physiotherapeutic treatment. Objective: To evaluate the results of the use of functional games in the preprotection of patients with post-osteosarcoma hip disarticulation. Methodology: The sample was composed of 1 adolescent, male gender. It was applied performance evaluation muscle strength, balance and motor coordination through the Videogame Xbox 360 accompanied by the Kinect sensor, with the Adventure da brand Microsoft game. Made 11 sessions. For analysis, we used the statistical program Microsoft Office Excel 2010 and the table of therapeutic planning before and after intervention. Results: There was a significant difference in all the previously established objectives, when the means were compared in relation to the evaluation performed in the initial section and the final evaluation performed after the eleventh sessions. Conclusion: It is concluded that the present study showed that the Kinect therapy proved to be effective to the previously established objectives that were to analyze the influence of the same before the force, motor coordination and balance in unilateral amputee disarticulation of post-osteosarcoma hip.